Sergio F. Martínez, Geografía de las prácticas científicas. Racionalidad, heurística y normatividad - J. Francisco Álvarez (Crítica)
Sergio F. Martínez, Geografía de las prácticas científicas. Racionalidad, heurística y normatividad